2017
DOI: 10.1371/journal.pntd.0005704
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-dependent differences in the disease progression of Zika virus infection in type-I interferon receptor knockout (A129) mice

Abstract: Zika virus (ZIKV) falls into two lineages: African (ZIKVAF) and Asian (ZIKVAS). These lineages have not been tested comprehensively in parallel for disease progression using an animal model system. Here, using the established type-I interferon receptor knockout (A129) mouse model, it is first demonstrated that ZIKVAF causes lethal infection, with different kinetics of disease manifestations according to the challenge dose. Animals challenged with a low dose of 10 plaque-forming units (pfu) developed more neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 59 publications
7
46
0
Order By: Relevance
“…We also confirmed that ZIKV Currently, there are two principal lineages of ZIKV strains, the African (MR766) and Asian (PRVABC59) lineages (Haddow et al, 2012;Yun et al, 2016). Accumulating reports suggest that lineage-dependent differences exist in the disease progression of ZIKV infection (Dowall et al, 2017). To evaluate the effect of various ZIKV strains on proliferation of human skin cells, HDFs and HaCaT keratinocytes were infected with the ZIKV strains MR766 or PRVABC59 at a multiplicity of infection of 1 for different time periods.…”
Section: Zikv Nonstructural Proteins Interact With Rlrs and Suppress supporting
confidence: 77%
“…We also confirmed that ZIKV Currently, there are two principal lineages of ZIKV strains, the African (MR766) and Asian (PRVABC59) lineages (Haddow et al, 2012;Yun et al, 2016). Accumulating reports suggest that lineage-dependent differences exist in the disease progression of ZIKV infection (Dowall et al, 2017). To evaluate the effect of various ZIKV strains on proliferation of human skin cells, HDFs and HaCaT keratinocytes were infected with the ZIKV strains MR766 or PRVABC59 at a multiplicity of infection of 1 for different time periods.…”
Section: Zikv Nonstructural Proteins Interact With Rlrs and Suppress supporting
confidence: 77%
“…Viremia decreased between days 2 and 6 p.i., as previously reported in several studies (55, 70, 71) but not in others (29, 56) for reasons that have not been discussed and remain unclear. In our study, the rate of decrease, which was estimated as the difference in viral load between day 2 and day 6 p.i., showed remarkable homogeneity between individuals of the same CC strain and very large variations across CC strains.…”
Section: Discussionmentioning
confidence: 59%
“…In the type-I interferon receptordeficient mouse model, ZIKV AF causes severe disease, whereas a much milder infection was seen after challenge with ZIKV AS [30]. Studies showed that there are strain-specific virulence differences between the African and Asian lineages in ZIKV mouse models [31]. Comparing the clinical findings between infected animals with different lineages of the viruses may help to understand the impact of genomic evolution and divergence and to surveillance by analyzing their sequences periodically.…”
mentioning
confidence: 99%